Optical and Structural Characteristics of Pterocarpus soyauxii Dye Sensitized TiO2 Thin Films - Usha Rajalakshmi*, P.; Oommen, Rachel; Vaishnavi, E. (Asian Journal of Chemistry, 2013)
Titanium dioxide thin films are deposited by successive ionic layer adsorption and reaction method. The films are annealed at 250 and 350 ºC. The natural dye obtained from Pterocarpus soyauxii is used for the sensitization of the films. TiO2 thin films are characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, UV-visible spectroscopy and photoluminescence spectroscopy. The XRD analysis reveals the polycrystalline (anatase) nature of the films. The film is stoichiometric and found to have porous microstructure. A red shift is observed in the band gap of the film upon dye sensitization. The film deposited at a lower growth rate exhibited a larger red shift when compared to the films deposited at higher growth rate. Absorption coefficient of the material is also found to be enhanced upon dye sensitization. The material exhibited luminescence and the strong peak observed at 2.98 nm is attributed to the Wannier-Mott free exciton emission.